PENGARUH TIKTOK TERHADAP CONSUMER IMPULSIF BUYING ONLINE BEHAVIOR PRODUK UMKM WANITA MADURA - Solihin, Solihin; Suyono, Suyono (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
TikTok is one of the most used social media platforms popular among young adults and teens and has over 1.4 billion monthly active users by 2023. Indonesia itself ranks second in the world for TikTok users, with monthly active users reaching 99.1 million people in April 2022. TikTok is enjoying significant growth in user acquisition with an increase in brands appearing on the platform. This study studies how TikTok affects the impulse buying behavior of consumers of Madura MSME products through the lens of the Stimulus-Organism-Response (SOR) model consisting of product-related visual appeal and product feasibility (Stimuli), perceived enjoyment, (Organism), and impulse purchase intention (Response) Smart PLS is used to analyze respondent response data from closed questionnaires distributed through online channels. The findings suggest that the visual appeal and feasibility of the product positively affect perceived enjoyment. The data confirms the positive effect perceived enjoyment among TikTok users has on their impulse buying behavior. In addition to theoretical implications and suggestions for expanding the research domain, the study offers practical recommendations for marketers to leverage TikTok's ability to drive impulse buying behavior